Electrical behavior of silver particulate films deposited on 8 MeV electron beam irradiated softened polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Journal of Materials Science-Materials in Electronics, 2011)
Results of the investigations carried out on the electrical behavior of silver particulate films deposited on electron beam irradiated polystyrene (PS) coated substrates held at a temperature of 455 K in a vacuum of 8 x 10(-6) torr at a constant deposition rate of 0.4 nm/s are reported. It is known that when metals are evaporated on to softened polymer substrates, subsurface particulate structures are formed whose morphology is dependent on deposition parameters. Further, it was shown that the morphology is dependent on polymer-metal interaction. The present work demonstrates that the polymer-metal interaction can be brought about in inert polymers like PS by electron irradiation. The results indicate that the films deposited on PS irradiated to a dose of 20 and 25 kGy gives rise to smaller clusters with smaller inter-cluster separation, better suited for sensor applications. The induced polymer-metal interaction is attributed to the creation of free radicals due to the 8 MeV electron irradiation.

Morphological changes in nanoparticulate silver films due to electron beam irradiation of polystyrene substrates - Pattabi, Manjunatha; Gurumurthy, S. C.; Sanjeev, Ganesh; Gaikwad, A. B. (Nuclear Instruments & Methods in Physics Research Section B-Beam Interactions With Materials and Atoms, 2011)
Results of the studies on the effect of 8 MeV electron beam irradiation of polystyrene substrates on the morphology of silver particulate films deposited at 455 K in a vacuum of 8 x 10(-6) Torr are reported. Optical absorption studies show the presence of transverse and longitudinal plasmon resonance for films deposited on irradiated polystyrene. Scanning electron microscopy reveals a decrease in particle size with smaller inter-particle separation for irradiated films. Larger clusters are formed in the case of films deposited on polystyrene after 300 h of irradiation. In this paper, we show that the morphology of silver nanoparticulate films can be modified by electron irradiation of inert polymer substrates like polystyrene. The change observed due to irradiation is attributed to the formation of free radicals, thereby altering the polymer-metal interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Electron bombardment; Optical properties; Particulate films; Polymers; Silver; surface morphology

Preparation and characterization of silver particulate films on softened polystyrene and poly(4-vinylpyridine) blends - Gurumurthy, S. C.; Pattabi, Manjunatha; Krishna, Shreedhar; Gaikwad, A. B. (Journal of Materials Science-Materials In Electronics, 2014)
Results of the investigations carried out on the optical properties of silver particulate films deposited at a rate of 0.4 nm/s on softened polystyrene and poly(4-vinylpyridine) (P4VP) blends held at 455 K are reported. Under the conditions of deposition, a sub-surface particulate structure is expected. It had been shown earlier that the morphology of the sub-surface particulate structure is dependent on polymer-metal interaction. In the present studies, an inert polymer like polystyrene (PS) is blended with an interacting polymer P4VP. The optical studies on the silver particulate films deposited on softened blends of PS/P4VP have been carried out. The results show a shift in plasmon resonance to higher wavelength with increasing P4VP concentration of the blends in comparison to that of the films deposited on pure PS. An X-ray photoelectron spectroscopy study at two different electron take off angles indicates the formation of subsurface particulate structures for films deposited on blends.

Advanced zinc-polymer composites for marine corrosion protection and self-healing - Sharma, Sanjay; Girish, Santhosh; Nayaka, G. P.; Shiva Samhitha, S.; Pilliadugula, Rekha; Shivamurthy, B. P.; Gurumurthy, S. C.; Ruiz-Robles, Mitchel A.; Rojas, D.; Surabhi, Srivathsava (NPJ Materials Degradation, 2025)
Steel corrosion in saltwater costs over \$2.5 trillion annually. This review highlights advancements in zinc and polymer-based coatings for marine protection. It covers traditional methods and emerging technologies like nanoparticle-enhanced alloys, conducting polymers, metal organic frameworks (MOFs), and 2D materials. These offer improved resistance, self-healing, and intelligent protection with a future focus on sustainability and extended service life for marine infrastructure.